Gitelman Syndrome in a 32-Years-Old Female Patient - Andikha Putra; Harnavi Harun (HM Publisher, 2022)
Introduction. Gitelman syndrome is an autosomal recessive disorder that is milder than Bartter syndrome and is often not diagnosed until late childhood or even adulthood. However, this syndrome is usually symptomatic and can result in serious clinical manifestations, such as muscle spasms that can be severe and involve the hands and feet. These symptoms are frequently observed in almost all patients, partly due to hypokalemia and hypomagnesemia. Case presentation. A 32-year-old female patient is being treated in the Internal Medicine ward of Dr. M. Djamil Padang General Hospital with the main complaint of cramping of the left hand, which has gotten worse since 1 day ago. The patient also complained that both legs were prone to cramping that went on and on since 1 month ago. The patient had been hospitalized with the same complaint and is currently taking slow release potassium (KSR) medication. Examination of the patient's limbs revealed a positive trousseau sign and carpopedal spasms. Laboratory examination of the patient showed potassium levels of 1.8 mmol/L, calcium levels of 5.7 mg/dl, Magnesium levels of 0.8 mg/dl, and electrolyte disturbances in the patient's urine. ECG results revealed a prolonged QT interval. Conclusion. Gitelman syndrome is an autosomal recessive disorder and often goes undiagnosed. However, this syndrome is usually symptomatic and can lead to serious clinical manifestations. Most patients require oral potassium and magnesium supplementation, as drug therapy is usually not fully effective.